"They're Not True Humans:" Beliefs about Moral Character Drive Denials of Humanity. Issue 2 (7th February 2022) - Phillips, Ben
Abstract: A puzzling feature of paradigmatic cases of dehumanization is that the perpetrators often attribute uniquely human traits to their victims. This has become known as the "paradox of dehumanization." I address the paradox by arguing that the perpetrators think about their victims as human in one sense, while denying that they are human in another sense. I do so by providing evidence that people harbor a dual character concept of humanity. Research has found that dual character concepts have two independent sets of criteria for their application, one of which is descriptive and one of which is normative. Four experiments provided evidence that people deploy a descriptive criterion according to which being human is a matter of being a Homo sapiens ; as well as a normative criterion according to which being human is a matter of possessing a deep‐seated commitment to do the morally right thing. Importantly, I found that people are willing to affirm that someone is human in the descriptive sense, while denying that they are human in the normative sense, and vice versa. In addition to providing a solution to the paradox of dehumanization, these findings suggest that perceptions of moral character have a central role to play in driving dehumanization.